Comparing sport motivation scales: A response to Pelletier et al. - Lonsdale, C.; Hodge, K.; Hargreaves, E. A.; Ng, J. Y. Y. (Psychology of Sport and Exercise, 2014)
Objectives: Pelletier, Rocchi, Vallerand, Deci, and Ryan (2013) proposed a new version of the Sport Motivation Scale (SMS; ) as a measure of different types of behavioral regulations in sport, as outlined in self-determination theory (Ryan & Deci, 2000). They examined various aspects of reliability and validity of scale scores, and concluded that the new scale performs better than the original version. They also claimed that the SMS-II is superior to other measures of motivation in sport, including the Behavioral Regulation in Sport Questionnaire (BRSQ) developed by . By comparing the evidence presented in papers by Pelletier et al. and Lonsdale et al., our objective was to examine the relative merits and shortcomings of the two measures and suggest directions for future research into sport motivation measurement. Conclusions: Both the SMS-II and BRSQ have shown relative strengths and weaknesses. Overall, the construct validity evidence of scores derived from the two measures was similar. There is insufficient information to support the claim that one scale is superior to the other. Researchers are encouraged to make direct comparisons by administering both measures to the same group of participants in future studies.